2019
DOI: 10.1139/bcb-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling and inhibitor docking analysis of the Na+/H+exchanger isoform one

Abstract: Na/H exchanger isoform one (NHE1) is a mammalian plasma membrane protein that removes intracellular protons, thereby elevating intracellular pH (pH). NHE1 uses the energy of allowing an extracellular sodium down its gradient into cells to remove one intracellular proton. The ubiquitous protein has several important physiological and pathological influences on mammalian cells as a result of its activity. The three-dimensional structure of human NHE1 (hNHE1) is not known. Here, we modeled NHE1 based on the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“… 10 Such an interaction resembles that of acylguanidine-based NHE1 inhibitors, such as amiloride, cariporide, zoniporide, and others. 44 , 45 The inhibitory potency of such drugs is related to (i) the ionization state of the acylguanidine group, which is cationic at acidic pH and (ii) structure, which resembles that of a tri-hydrated Na + ion. 29 , 44 A new class of non-acylguanidine inhibitors has been recently described (SL591227 46 and 9t 47 ) that is predicted to bind NHE1 via their imidazole motif, a surrogate for the acylguanidine group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Such an interaction resembles that of acylguanidine-based NHE1 inhibitors, such as amiloride, cariporide, zoniporide, and others. 44 , 45 The inhibitory potency of such drugs is related to (i) the ionization state of the acylguanidine group, which is cationic at acidic pH and (ii) structure, which resembles that of a tri-hydrated Na + ion. 29 , 44 A new class of non-acylguanidine inhibitors has been recently described (SL591227 46 and 9t 47 ) that is predicted to bind NHE1 via their imidazole motif, a surrogate for the acylguanidine group.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 The inhibitory potency of such drugs is related to (i) the ionization state of the acylguanidine group, which is cationic at acidic pH and (ii) structure, which resembles that of a tri-hydrated Na + ion. 29 , 44 A new class of non-acylguanidine inhibitors has been recently described (SL591227 46 and 9t 47 ) that is predicted to bind NHE1 via their imidazole motif, a surrogate for the acylguanidine group. 46 , 48 Since EMPA does not possess either of these motifs, an interaction with NHE1 would be surprising and certainly not canonical.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the region containing amino acids, when phosphorylated, binds to this proximal region and affects NHE1 activity. Amino acids 501–524 are predicted to be close to the lipid bilayer [ 40 ] which might indicate they are in proximity of the intracellular face of the pore of the protein. The binding of a more distal region of the cytoplasmic tail could certainly affect transport, and in this study, we showed that these mutations do modulate NHE1 function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a gate exists in NHE1 that is closed upon autoinhibitory interactions with the region of the C-terminal tail [34]. However, this mechanism is based on the model of NHE1, which originated from NhaA, and others have more recently suggested that NhaA is too different from NHE1 to be used as a model [79]. Nevertheless, it seems likely that the tail must interact with the membrane domain to affect function, and regulation by phosphorylation and proteins seem likely to affect this.…”
Section: Discussionmentioning
confidence: 99%
“…Later work suggested that amino acids 363–410 are EL5, with amino acids 341–362 preceding it as TM9 [77,78]. Recently, a newer molecular modeling of NHE1 also mapped amino acids 363–410 to the extracellular surface and also docked NHE inhibitors to sites on the protein [79]. The region between TM9 and TM10 (extracellular loop 5, approximately amino acids 362–411) was shown to be extracellular based on cysteine scanning and accessibility experiments.…”
Section: Introductionmentioning
confidence: 99%